RETRACTED: Methods of social network texts analysis for a psychometric model of personal behavior - Prokopyev Nikolai; Ustin Pavel; Gafarov Fail; Popov Leonid (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001